Leadership Strategies in Improving the Effectiveness of Educational Programs in Nurul Jadid Student Dormitory (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
Educational institutions play a crucial role in the preparation of quality human resources. The success of education is measured through the achievement of its goals and effectiveness. Successful education achieves goals with results as planned. Effective leadership in educational institutions can increase the effectiveness of educational programs. This study aims to analyze the leadership strategy of the dormitory head in improving the effectiveness of educational programs at the Nurul Jadid Student Dormitory. This research uses a qualitative approach with primary data from interviews and observations and secondary data from reports and documentation. The main informants are the head of the dormitory and the dormitory administrator. The analysis focused on the leadership strategy of the head of the dormitory to support the effectiveness of the education program. The results showed that the head of the dormitory implemented strategies to improve the effectiveness of the education program. One of them is involving experts in various fields in religious activities, such as Koran guidance, book recitation, and seminars. The presence of experts aims to improve the quality of education and provide deep insight. In addition, the head of the dormitory established a partnership with the head of the boarding school to strengthen the religious aspects of students.